Sodium Bicarbonate versus N-Acetylcysteine plus hydration versus hydration alone for preventing contrast-associated acute kidney injury: A single-center retrospective analysis with propensity score matching - Ying-Huan Ma; Wei Wei; Nan Li; Yan Sun; Xiao-Xu Chen; Xiu-Ying Hao; Ai-Guo Xie (PLoS ONE, 2026)
Background Contrast-associated acute kidney injury (CA-AKI, historically termed contrast-induced nephropathy, CIN) is a leading cause of iatrogenic acute kidney injury (AKI) following iodinated contrast administration; yet the optimal preventive strategy remains controversial, especially in mild-to-moderate-risk patients. Methods This single-center retrospective observational study was conducted in strict accordance with the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. We consecutively screened adult patients undergoing contrast-enhanced computed tomography (CT) or angiography at a tertiary hospital in China between June 2022 and January 2025. After propensity score matching (PSM), 240 adult patients were included in the final analysis, allocated 1:1:1 into three groups: conventional hydration alone (control), hydration plus N-acetylcysteine (NAC), and hydration plus sodium bicarbonate. 1:1:1 nearest-neighbor PSM was performed to minimize confounding bias, with a caliper of 0.05. The primary endpoint was the incidence of CA-AKI within 72 hours after contrast exposure, defined per the 2024 European Society of Urogenital Radiology (ESUR) guidelines. Secondary endpoints included dynamic changes in renal function, renal replacement therapy (RRT) requirement, hospital stay duration, adverse events, and subgroup analyses by comorbidities and contrast modalities. Results After PSM, 240 patients (80 per group) were included in the final analysis, with well-balanced baseline characteristics across groups (all standardized mean differences <0.1, all P > 0.05). The overall incidence of CA-AKI was 15.00% in the control group, 2.50% in the NAC group, and 7.50% in the sodium bicarbonate group. Hydration plus NAC significantly reduced CA-AKI risk compared with hydration alone (RR = 0.17, 95% CI: 0.04–0.74, Bonferroni-adjusted P = 0.004). Sodium bicarbonate showed a numerically lower CA-AKI incidence than control, but the difference did not reach statistical significance after correction (RR = 0.50, 95% CI: 0.19–1.31, adjusted P = 0.121). Repeated-measures ANOVA revealed significant group, time, and group × time interaction effects on serum creatinine (Scr), blood urea nitrogen (BUN), and estimated glomerular filtration rate (eGFR) (all P < 0.001), with the mildest renal function fluctuations in the NAC group. The renoprotective efficacy of NAC was consistent across contrast-enhanced CT and angiography modalities. Advanced age, comorbid diabetes, comorbid hypertension, higher baseline Scr, and lower baseline eGFR were independent risk factors for CA-AKI [5,6,28] (all P < 0.05). No patients required RRT in any group, with no significant difference in hospital stay duration or mild adverse event incidence across groups (all P > 0.05). Conclusions For patients with eGFR ≥ 30 mL·min ⁻ ¹·(1.73 m² ⁻ ¹), hydration combined with high-dose intravenous NAC significantly reduces the short-term incidence of CA-AKI compared with hydration alone, with a favorable safety profile and consistent efficacy across contrast modalities. Hydration plus sodium bicarbonate is a safe alternative for patients intolerant to NAC. These findings are hypothesis-generating and require verification in large-sample, multicenter prospective trials.